Pengaruh Model Contextual Teaching and Learning (CTL)Pada Topik Konservasi Lingkungan Sekitar Sekolah Untuk Mendukung Literasi STEM Siswa SMP Kelas VII - Nurul Fadhilah; R Ahmad Zaky El Islami; Septi Kurniasih (PendIPA Journal of Science Education, 2026)
STEM literacy is an essential skill for students in the 21st century; however, its level remains relatively low among junior high school students. The Contextual Teaching and Learning (CTL) model offers a potential approach to improve this ability. This study aimed to analyze the effect of CTL on seventh-grade students’ STEM literacy and examine differences in STEM literacy improvement between students taught using CTL and Discovery Learning. A quasi-experimental method with a nonequivalent control group design was employed. The participants were 74 seventh-grade students from a public junior high school in Serang City, divided equally into experimental and control classes. The instruments consisted of a STEM literacy test based on six indicators proposed by Pitiporntapin et al. (2023), an observation sheet, and a student response questionnaire. Data were analyzed using the Mann–Whitney U test due to non-normal distribution. The results showed that CTL had a significant effect on students’ STEM literacy, with an Asymp. Sig. (2-tailed) value of 0.000 < 0.05. A significant difference in STEM literacy improvement was also found between the experimental and control classes (0.000 < 0.05). CTL implementation reached 100%, while students’ responses were very positive, with an average score of 84.35%. These findings confirm that CTL is effective in enhancing STEM literacy among seventh-grade students in the context of environmental conservation around the school.